Pengaruh Pengungkapan Tanggung Jawab Sosial dan Lingkungan (TJSL), Pertumbuhan Penjualan, dan Intensitas Modal terhadap Nilai Perusahaan - Alya Zhafira; Dwi Astuti, Christina (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to explore the connection between corporate social responsibility (TJSL) disclosure, sales growth, and capital intensity in relation to firm value, incorporating profitability and leverage as control variables. The research takes a quantitative approach, analyzing secondary data and focusing on companies in the consumer non-cyclical sector listed on the Indonesia Stock Exchange from 2018 to 2022. Through purposive sampling, 198 observational samples were gathered between 2018 and 2022. The data analysis, conducted using the SPSS version 29.0 program, involved multiple linear regression analysis. The findings highlight a significant positive impact of capital intensity on firm value. However, corporate social responsibility disclosure and sales growth show no noticeable effect on firm value based on the results of this study.